Improving Student Learning Outcomes in Social Studies Learning Using the Quantum Teaching Model in Elementary School - Fadhilah Fadhilah; Yeni Erita; Rahmi YULIA (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This study aims to see the increase in social studies learning outcomes with the Quantum Teaching model in grade IV elementary school at SDN 13 Padang Gelanggang, as many as 20 students consisting of 12 male students and 8 female students. Based on the results of this study, learning was very low, because the teacher only talk in learning, because of that students become lazy. The purpose of this study is to improve the student learning process by using the Quantum Teaching model , including learning preparation. This research uses Qualitative and Quantitative. Based on the results of the analysis in 2 cycles, the results obtained in 2 cycles increased the number of lesson plans from 76.78 to 92.85. For teacher activity , from 75 to 89.06. Judging from student activity from 68 .81 to 84.36, the number of cognitive learning 80, affective 81.15, psychomotor 85.55. It can be concluded that learning with the Quantum Teaching model increases. So it can be concluded that there is an increase in class IV student learning outcomes in social studies learning using the Quantum Teaching Model